Flow chemistry-enabled asymmetric synthesis of cyproterone acetate in a chemo-biocatalytic approach - Yajiao Zhang; Minjie Liu; Xianjing Zheng; Liang Gao; Li Wan; Dang Cheng; Fener Chen (Nature Communications)
Abstract Flow chemistry has many advantages over batch synthesis of organic small-molecules in terms of environmental compatibility, safety and synthetic efficiency when scale-up is considered. Herein, we report the 10-step chemo-biocatalytic continuous flow asymmetric synthesis of cyproterone acetate (4) in which 10 transformations are combined into a telescoped flow linear sequence from commercially available 4-androstene-3, 17-dione (11). This integrated one-flow synthesis features an engineered 3-ketosteroid-Δ1-dehydrogenase (ReM2)-catalyzed Δ1-dehydrogenation to form the C1, C2-double bond of A ring, a substrate-controlled Co-catalyzed Mukaiyama hydration of 9 to forge the crucial chiral C17α-OH group of D ring with excellent stereoselectivity, and a rapid flow Corey-Chaykovsky cyclopropanation of 7 to build the cyclopropyl core of A ring. By strategic use of these three key reactions and fully continuous-flow operations, cyproterone acetate (4) is produced in an overall yield of 9.6% in 3 h of total reaction time, this is the highest total number of chemical transformation performance in any other continuous-flow synthesis reported to date.